3-D simulation of posterior fossa reduction in Chiari I - Yvens Barbosa Fernandes; Pedro Fábio Mendonça Perestrelo; Pedro Yoshito Noritomi; Roger Neves Mathias; Jorge Vicente Lopes da Silva; Andrei Fernandes Joaquim (Arquivos de Neuro-Psiquiatria)
ABSTRACT We proposed a 3D model to evaluate the role of platybasia and clivus length in the development of Chiari I (CI). Using a computer aided design software, two DICOM files of a normal CT scan and MR were used to simulate different clivus lengths (CL) and also different basal angles (BA). The final posterior fossa volume (PFV) was obtained for each variation and the percentage of the volumetric change was acquired with the same method. The initial normal values of CL and BA were 35.65 mm and 112.66º respectively, with a total PFV of 209 ml. Ranging the CL from 34.65 to 29.65 – 24.65 – 19.65, there was a PFV decrease of 0.47% – 1.12% – 1.69%, respectively. Ranging the BA from 122.66º to 127.66º – 142.66º, the PFV decreased 0.69% – 3.23%, respectively. Our model highlights the importance of the basal angle and clivus length to the development of CI.